2007
DOI: 10.2478/s11696-007-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of fructosyltransferase from Aureobasidium pullulans immobilized on an acrylic carrier

Abstract: Optimization of immobilization conditions was carried out for covalent binding of Aureobasidium pullulans fructosyltransferase to a copolymer of butyl acrylate and ethylene glycol dimethacrylate using a glutaraldehyde method. It was found that the highest activity of the preparation could be obtained for the immobilization pH 6.0 and initial protein amount 8.5 g per dm3 of the carrier. Effects of the reaction pH, temperature, and initial sucrose concentration on the activity and stability of the preparation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…immobilized onto niobium ore showed high activity and good stability at pH from 4.5 to 6.0 6 . Similarly, the FTase from Aureobasidium pullulans CCY 27–1‐94 immobilized on an acrylic carrier showed relative activity higher than 85% at pH values from 3 to 6 after 1 h of incubation 67 …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…immobilized onto niobium ore showed high activity and good stability at pH from 4.5 to 6.0 6 . Similarly, the FTase from Aureobasidium pullulans CCY 27–1‐94 immobilized on an acrylic carrier showed relative activity higher than 85% at pH values from 3 to 6 after 1 h of incubation 67 …”
Section: Resultsmentioning
confidence: 93%
“…5). Specifically, pH inactivation of enzymes involves the unfolding of the protein molecule due to changes in the electrostatic balance and hydrogen bonds that increase due to a pH‐induced change of the ionization state of the enzyme ionogenic group 67 . It was reported that the FTase from A. oryzae IPT‐301 immobilized by adsorption on silica gel showed high stability at pH values from 5.0 to 6.5, with relative activity higher than 95% 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, various carriers and methodologies have been used for enzyme immobilization in order to improve the properties of free enzyme [8][9][10][11]. In fact, the performance of immobilized lipase relies on several important factors including immobilization methods, immobilization carrier materials, enzyme pretreatment before immobilization, and enzyme loading on the carriers.…”
Section: Introductionmentioning
confidence: 99%